EPJ Techniques and Instrumentation - Buckman, Stephen J.; Grütter, Peter; Hegner, Martin
EPJ Techniques and Instrumentation focuses on the design, implementation, and application of new techniques in all areas of the physical and applied sciences. Of particular interest to the journal are advances produced by: Laboratory-specific custom instrumentation and diagnostics Innovative and clever experimental techniques Subtle refinements to established experimental setups Novel analytical methods Papers in the journal should summarize a novel, significant result, and provide a detailed description of the equipment, methods, or techniques used to produce the result. They may also include discussions of underlying theory, and/or potential cross-disciplinary applications. EPJ Techniques and Instrumentation publishes regular articles, as well as short commentary articles intended to promote discussion and debate. Reviews of known techniques, or of open questions in emerging fields, are also strongly encouraged. This fully Open Access journal is devoted to the broad, timely, and public dissemination of information.